2020
DOI: 10.1029/2020gl087008
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Momentum and False Alarms in Late‐Spring ENSO Forecasts

Abstract: The unanticipated stalled El Niño-Southern Oscillation (ENSO) evolution of 2014 raises questions about the reliability of the coupled models that were used for forecast guidance. Here we have analyzed the skill and reliability of forecasts of the Niño 3.4 tendency (3-month change) in the North American multimodel ensemble . We found that forecasts initialized April-June (AMJ) have "excessive momentum" in the sense that the forecast Niño 3.4 tendency is more likely to be a continuation of the prior observed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…There is recent evidence that, in initialized seasonal climate prediction models, El Niño false alarms have increased in the last half of the 1982-2020 record 179 , and this may be tied to errors in simulated linear SST trends across the equatorial Pacific Ocean 36,180 . As described earlier, many state-of-the-art seasonal climate prediction models have stronger positive trends in the central and eastern tropical Pacific than found in the observations.…”
Section: Consequences Of Equatorial Pacific Sst Trendsmentioning
confidence: 99%
“…There is recent evidence that, in initialized seasonal climate prediction models, El Niño false alarms have increased in the last half of the 1982-2020 record 179 , and this may be tied to errors in simulated linear SST trends across the equatorial Pacific Ocean 36,180 . As described earlier, many state-of-the-art seasonal climate prediction models have stronger positive trends in the central and eastern tropical Pacific than found in the observations.…”
Section: Consequences Of Equatorial Pacific Sst Trendsmentioning
confidence: 99%
“…Instead, following the approach in Tippett et al (2020), we evaluated the skill of the tendency of both SST and SSH anomalies over the 6 months after initialization [i.e., the skill of    …”
Section: Assessing the Impact Of The Secular Trend On Skillmentioning
confidence: 99%
“…Instead, following the approach in Tippett et al. (2020), we evaluated the skill of the tendency of both SST and SSH anomalies over the 6 months after initialization [i.e., the skill of x(6)x(0) rather than boldx(6)]. This skill metric removes the impact of the trend component, to the extent that it is relatively constant over any 6‐month increment, as is largely the case for the LIM.…”
Section: Hindcast Skill Evaluationmentioning
confidence: 99%
“…These are El Niño events which are predicted by the models, but end up failing to occur in reality. Tippett et al (2020) identified several El Niño false alarms while analyzing model "excessive momentum, " in which the observed Niño-3.4 SST index tendency during the spring is too strongly correlated with the forecast tendency of ENSO into the fall. In other words, positive springtime changes in the observed Niño-3.4 index often beget a positive forecast trajectory in the Niño-3.4 index.…”
Section: Relating Recent El Niño False Alarms With Errors In Trends O...mentioning
confidence: 99%
“…In other words, positive springtime changes in the observed Niño-3.4 index often beget a positive forecast trajectory in the Niño-3.4 index. Tippett et al (2020) showed that out of all springtime busts during 1982-2018, four of nine occurred in the last decade (2011, 2013, 2014, and 2017) and they were all El Niño false alarms-a concerning development for seasonal climate forecasting if it continues.…”
Section: Relating Recent El Niño False Alarms With Errors In Trends O...mentioning
confidence: 99%